2021
DOI: 10.1101/2021.03.04.433866
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Probing interoception via thermosensation: No specific relationships across multiple interoceptive sub-modalities

Abstract: Interoception, i.e., the perception of the physiological status of the body, includes signals originating both from inside the body and from its surface, the skin. Here, we focused on the perception of temperature, a crucial modality for the maintenance of homeostasis. We used a classic thermal detection task and developed a new thermal matching task, in which participants were asked to match a previously perceived moving thermal stimulus applied to their skin to a range of colder or warmer stimuli, presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 108 publications
(208 reference statements)
0
4
1
Order By: Relevance
“…It has also been proposed that blind individuals might rely more on internal hunger cues rather than taste in food choices (Gagnon, Kupers, & Ptito, 2013). Although it may suggest that the current findings could be generalizable, recent studies in sighted individuals have found that perceptual abilities on different interoceptive tasks that probe different submodalites are independent and uncorrelated (Garfinkel et al, 2016b; Ferentzi et al, 2018; Crucianelli, Enmalm, & Ehrsson, 2021) and that cardiac interoceptive accuracy does not correlate significantly with accuracy measures in skin-based interoceptive tasks (Crucianelli et al, 2021). Thus, to obtain a more complete picture of how visual deprivation affects interception, future studies should employ a battery of tests and investigate how different interoceptive submodalities are affected by visual deprivation and if some are more influenced than others.…”
Section: Discussioncontrasting
confidence: 68%
“…It has also been proposed that blind individuals might rely more on internal hunger cues rather than taste in food choices (Gagnon, Kupers, & Ptito, 2013). Although it may suggest that the current findings could be generalizable, recent studies in sighted individuals have found that perceptual abilities on different interoceptive tasks that probe different submodalites are independent and uncorrelated (Garfinkel et al, 2016b; Ferentzi et al, 2018; Crucianelli, Enmalm, & Ehrsson, 2021) and that cardiac interoceptive accuracy does not correlate significantly with accuracy measures in skin-based interoceptive tasks (Crucianelli et al, 2021). Thus, to obtain a more complete picture of how visual deprivation affects interception, future studies should employ a battery of tests and investigate how different interoceptive submodalities are affected by visual deprivation and if some are more influenced than others.…”
Section: Discussioncontrasting
confidence: 68%
“…The study was conducted in accordance with the provisions of the Declaration of Helsinki 1975, as revised in 2008. Part of the data obtained in Experiment 1 was analyzed using a different statistical method for different purposes and has been published as part of another manuscript (Crucianelli, Enmalm & Ehrsson, 2021).…”
Section: Participantsmentioning
confidence: 99%
“…Consistent with the idea of affective touch as an interoceptive modality, our results showed that higher cardiac interoceptive accuracy as measured by means of a classic heartbeat counting task (Schandry, 1981) was related to a better fit of the negative quadratic model for the perception of touch on hairy skin (with a similar but non-significant statistical trend observed for non-hairy skin). In this regard, recent studies have reported non-significant relationships between the perception of affective touch and cardiac interoceptive accuracy (Crucianelli et al, 2018;Crucianelli, Enmalm & Ehrsson, 2021); however, interoceptive accuracy was a predictor of tactile pleasantness in a multisensory integration paradigm only when touch was delivered at the borderline velocity for CT optimality (9 cm/s, Crucianelli et al, 2018). Taken together, these findings suggest that the link between cardiac interoception and tactile pleasantness is more complex than originally thought, and modeling approaches might be better suited to describe such relationships.…”
Section: The Perception Of Affective Touch At the Individual Levelmentioning
confidence: 99%
“…However, although we exclude the processing of signals through the external surface of the skin, we acknowledge that homeostatically-relevant external stimulations can induce internal signals (e.g., Crucianelli et al, 2021). Thermal and painful external stimuli, as well as affective touch, are all instances of external stimulations inducing internal physiological consequences or affect (Björnsdotter et al, 2010;Craig, 2008).…”
Section: Our Recommended Definition and Its Implicationsmentioning
confidence: 99%